Enthalpy of vaporization and vapor pressure of whiskey lactone and menthalactone by correlation gas chromatography. (July 2017) - Simmons, Daniel; Chickos, James
Highlights: The vapor pressure and vaporization enthalpies of cis and trans -whiskey lactone have been evaluated. Enthalpies of vaporization and vapor pressures of (+)-isomintlactone and (−)-mintlactone were also evaluated. The sublimation enthalpy and corresponding vapor pressure of (+) -isomintlactone at T = 298.15 K is estimated. Abstract: Enthalpies of vaporization at T = 298.15 K of cis and trans -whiskey lactone have been evaluated by correlation gas chromatography to be (68.4 ± 1.7) kJ·mol −1 and (67.5 ± 1.7) kJ·mol −1, respectively. The enthalpies of vaporization of isomintlactone and mintlactone also evaluated by correlation gas chromatography have been found to have vaporization enthalpies of (74.2 ± 1.8) kJ·mol −1 and (73.2 ± 1.8) kJ·mol −1 respectively. The vapor pressures for cis and trans -whiskey lactone at T = 298.15 K have been evaluated as (1.5 ± 0.09) Pa and (2.0 ± 0.1) Pa using vapor pressures of a series of lactones as standards. Vapor pressures for isomintlactone and mintlactone were evaluated as (0.26 ± 0.012) Pa and (0.33 ± 0.02) Pa, respectively. Fusion and sublimation enthalpies for (+)-isomintlactone as well as the vapor pressure of the solid have been estimated.